Experience of using combined thermal and low-frequency stimulation in patients with lumbar sciatica - R. A. Bodrova; A. A. Ismagilova; A. R. Kamaleeva (Лечащий Врач)
Background. Pain in the lower back occupies one of the leading places among the reasons for visiting doctors of various specialties and disability of people of different age categories. Back pain limits life activity, reduces the quality of life of patients, changes the psyche and behavior of people. Only full-fledged rehabilitation allows one to restore previous motor activity and reduce the period of temporary disability among the working part of the population.   Objective. To investigate the effectiveness of combined hardware thermal and low-frequency therapy in medical rehabilitation of patients with lumbar sciatica.   Materials and methods. A retrospective analysis of statistical data was carried out on 90 patients in the department of medical rehabilitation of patients with dysfunction of the peripheral nervous system and the musculoskeletal system of the treatment and rehabilitation center of the State Autonomous Healthcare Institution "City Clinical Hospital No. 7 named after M. N. Sadykov" Kazan. Patients were randomly divided into two groups – I main (n = 45) and II control (n = 45). Patients of group I (main), against the background of standard therapy, received combined treatment using a thermotherapeutic personal stimulator massager N4 with accessories, including low-frequency stimulation through a myostimulation belt included in the package of the massager and roller massage with tourmanium rollers, which perform hardware massage of the back and lumbar region at a certain angle of the spine paravertebrally, as well as uniform distribution of heat and massage pressure; Group II (control) received standard treatment (physical therapy, classic massage of the back and lumbar region). The effectiveness of the measures taken was assessed based on the vertebrogenic status of patients before and after medical rehabilitation.   Results. More pronounced statistically significant positive dynamics at the end of the course of medical rehabilitation were noted in patients of group I (main): a decrease in pain syndrome on the VAS scale, the severity of scoliosis, and tension in the paravertebral muscles; increased range of motion in the lumbar spine. The level of anxiety on the HADS scale and Lasegue's symptom also decreased statistically significantly in patients of group I compared with group II (control).   Conclusion. The effectiveness of the use of the thermotherapeutic personal massager-stimulator N4 with accessories in the treatment of patients with lumbar ischialgia is supported by the results of a study showing that patients in group I (main) had a more significant improvement in the statodynamic function of the spine, a decrease in pain, the severity of scoliosis, anxiety and depression, an increase amplitude of movements in the lumbar spine compared to patients in group II (control) who received a course of treatment without a combined low-frequency thermal stimulator (p < 0.1).